2013
DOI: 10.1177/194008291300600505
|View full text |Cite
|
Sign up to set email alerts
|

Insect Functional Guilds in the Flowering Canopy of Myristica Fatua in a Lowland Swamp, Central Western Ghats, India

Abstract: Little is known of canopy insects and pollinators of the nutmeg family (Myristicaceae), despite its being a common pantropical tree family and a commercially-grown spice. To address this lack of knowledge, an assessment was made of the insect fauna associated with the canopy of Myristica fatua (Myristicaceae), an endemic tree species inhabiting the rare and endangered lowland 'Myristica' swamps of the south and central Western Ghats of India. Yellow Sticky Traps were hung in tree canopies to record insect dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Until then, the only study that reported small diverse insects in a nutmeg pollinator guild was the one on Neotropical Virola koschnyi [31]. In Myristica fatua, thrips (Thysanoptera: Phlaeothripidae and Thripidae) and beetles (Coleoptera: Curculionidae, Cleridae, Cucujidae, Cantharidae and Silvanidae) were found to be potential pollinators [52].…”
Section: Insect Visitors and Pollinatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Until then, the only study that reported small diverse insects in a nutmeg pollinator guild was the one on Neotropical Virola koschnyi [31]. In Myristica fatua, thrips (Thysanoptera: Phlaeothripidae and Thripidae) and beetles (Coleoptera: Curculionidae, Cleridae, Cucujidae, Cantharidae and Silvanidae) were found to be potential pollinators [52].…”
Section: Insect Visitors and Pollinatorsmentioning
confidence: 99%
“…With beetles, pollination is often combined with feeding on stigmatic secretions, anthers and pollen, staminodia, and perianth parts (phytophagy) [50]. Clearly, considerable overlap of functional guilds exists on tropical tree species, and relatively small, simple flowers of trees such as nutmegs can interact with a range of potential insect pollinators [52].…”
Section: Insect Visitors and Pollinatorsmentioning
confidence: 99%